An efficient stream region sink position analysis model for routing attack detection in mobile ad hoc networks. (March 2019) - Vigenesh, M.; Santhosh, R.
Abstract: Under real-world conditions, simply finding the congestion or energy parameter in the hops of routes does not lead to efficient performance. Hence an efficient stream region sink position analysis (ESRSPA) model for improving attack detection in mobile ad hoc networks (MANETs) is developed. Attack detection is the process of identifying malicious nodes which are located in the system. A MANET has numerous nodes, which are free to move in any direction. The mobile nodes perform cooperative routing and elect the head node for receiving updates; this is known as sink position analysis. The nodes come under the stream position and send updates to the sink and other controlling nodes. In this manner, complete information can be traced and a set of actions be performed in various applications. The ESPRA reduces the routing overhead by 50% with a 96.86% throughput claims the ESPRA over other existing methods namely G-Hazard, FBRD, LFR-TA.